2022
DOI: 10.3390/foods11030322
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Isothermal Amplification Methods and Food-Origin Inhibitors against Detecting Food-Borne Pathogens

Abstract: The isothermal amplification method, a molecular-based diagnostic technology, such as loop-mediated isothermal amplification (LAMP) and recombinase polymerase amplification (RPA), is widely used as an alternative to the time-consuming and labor-intensive culture-based detection method. However, food matrices or other compounds can inhibit molecular-based diagnostic technologies, causing reduced detection efficiencies, and false-negative results. These inhibitors originating from food are polysaccharides and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 127 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…Moreover, Zhang et al demonstrated that the LAMP test can detect the DNA of M. bovis without any cross-reaction with other mycobacterial DNA, indicating a high Sp of the test [ 22 ]. However, the performance of the LAMP test may be affected by the high concentration of calcium ions in milk, which can competitively bind to DNA polymerases with magnesium ions, a necessary cofactor for the reaction [ 23 ]. Additionally, prior estimates of disease prevalence given in the current study are based on the reports of previous surveys using only the SIT test.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang et al demonstrated that the LAMP test can detect the DNA of M. bovis without any cross-reaction with other mycobacterial DNA, indicating a high Sp of the test [ 22 ]. However, the performance of the LAMP test may be affected by the high concentration of calcium ions in milk, which can competitively bind to DNA polymerases with magnesium ions, a necessary cofactor for the reaction [ 23 ]. Additionally, prior estimates of disease prevalence given in the current study are based on the reports of previous surveys using only the SIT test.…”
Section: Discussionmentioning
confidence: 99%
“…The complex components of food samples (Moon et al . 2022) as well as other pathogens in food might inhibit the nucleic acid amplification. Therefore, the artificially contaminated samples were detected by the PMA‐LAMP‐based visual assay developed in this study to determine the reliability.…”
Section: Resultsmentioning
confidence: 99%
“…The more the primers in the LAMP reaction, the higher the quality and integrity of the template required [ 29 , 30 ]. Moreover, seafood has been reported to contain some types of Bst polymerase inhibitors such as cationic polysaccharides and/or calcium ions that inhibit polymerase activity and competitively bind to Bst polymerases with magnesium ions [ 31 ]. Therefore, a DNA extraction method developed for food samples is required to obtain high-quality DNA [ 32 ].…”
Section: Discussionmentioning
confidence: 99%